Characterization of the largest relic Eurasian wild grapevine reservoir in Southern Iberian Peninsula - Arroyo-García, Rosa; Cantos, Manuel; Lara, Miguel; López, María-Ángeles; Gallardo, Antonio; Ocete, Carlos A.; Pérez, Ángeles; Bánáti, Hajnalka; García, José L.; Ocete, Rafael (Spanish Journal of Agricultural Research, 2016)
Wild grapevine is becoming a threatened species in the Iberian Peninsula due to human impacts. The aim of this work was to carry out a holistic study for six years of the largest wild grapevine population found up to date in SW Iberian Peninsula. This population has 115 vines. Ampelographic and soil characteristics have been studied. Evaluation of its environment has also been studied by describing the main parasitic species and natural enemies of pests. The ability of this plant material for its micropropagation and storage in slow-growth conditions has been tested. Microvinification resulted in a wine with good acidity and medium color intensity, two interesting characteristics under a warm climatology. Finally, the identification of private alleles in this wild population, absent in other locations from the Northern and Southern Iberian territories, is a very valuable feature and confirms the importance of establishing conservation programs. The population here studied is genetically unique and potentially useful for commercial rootstocks and cultivars breeding that would improve viticulture and enology.